Student information-seeking behavior in meeting Islamic information needs - Mudawamah, Nita Siti; Winata, Arda Putri; Sandra, Ferika (Universitas Padjadjaran, 2023)
The large number of Islamic tertiary institutions with a specific religious curriculum between one Islamic university and another. This curriculum is should be able to increase students’ knowledge of Islamic information for academic and non-academic needs. So, this study aimed to describe the behavior of Islamic students in Malang City using the Wilson model, including patterns of information-seeking behavior, sources used in seeking information, and evaluation of Islamic information. Method research was a qualitative study. Research subject involving nine informants consisting of students from UIN Maulana Malik Ibrahim, the Islamic University of Malang, and the University of Muhammadiyah Malang. This study described Islamic information-seeking behavior based on cognitive, affective, and physiological information needs. In addition, this study described information search patterns such as passive search, active search, and continuous search. This study concludes that students in seek Islamic information used diverse pattern. Information for academic purposes, primarily via books, scientific journal databases, and Google Scholar, and Islamic information to meet non-academic needs comes from YouTube, Instagram, and websites. Students can notice the information creator's background in examining online sources of information. Students evaluate Islamic information sources by comparing various sources obtained, asking friends who are considered qualified in religious knowledge, and directly asking the ustadz.